Exchange rates, capital flows and international trade : the case of Bangladesh - Hossain, Akhtar (Dhaka : University Press, 2000)
Business
Keywords: International trade; Exchange rates; Capital flows; Devaluation; Inflation; Global economyInstitutional development; Political stability; Economic stability